TINGKAT KECEMASAN MATEMATIKA (PERBEDAAN ANTARA SISWA YANG BELAJAR DENGAN ROTE LEARNING DAN INQUIRY LEARNING) - Rena Kristanti; Yapina Widyawati (MANASA, 2014)
Math is an important subject. It will improve student’s ability to thinklogically, analytically, and systematically. However, the process of learningmathematics often causes anxiety. Math anxiety is a feeling of inadequacy,tension, or panic when dealing with arithmetic operations and mathematicalproblems in a situation of academic and in everyday situations. One of the factors that cause mathematics anxiety is the learning methods which were notappropriate to make students understand mathematical concepts. Because of this they had an unpleasant experience while learning mathematics.Researchersexamined the level of mathematics anxiety among students who learn with rotemethod of learning and inquiry learning. Rote learning method is learningthrough memorizing a series of information without understanding the processand the relation between those concepts. Inquiry learning is a method thatencourages students to collect and analyze information, make decisions, buildtheir own understanding, create new things, and apply those concepts to solve problems. Researchers used a Children Math Anxiety Questionnaire (CMAQ). There were 175 students. The results show that there are significant differences in the level of mathematics anxiety among students who learn by rote learning and inquiry. Another factor that determines the math anxiety are the demands of the family and also the school for students to get high grades in math.